Expression and Function of Eicosanoid-Producing Cytochrome P450 Enzymes in Solid Tumors - Evangelista, Eric A.; Cho, Christi W.; Aliwarga, Theresa; Totah, Rheem A. (Frontiers in Pharmacology, 2020)
Oxylipins derived from the oxidation of polyunsaturated fatty acids (PUFAs) act as important paracrine and autocrine signaling molecules. A subclass of oxylipins, the eicosanoids, have a broad range of physiological outcomes in inflammation, the immune response, cardiovascular homeostasis, and cell growth regulation. Consequently, eicosanoids are implicated in the pathophysiology of various diseases, most notably cancer, where eicosanoid mediated signaling is involved in tumor development, progression and angiogenesis. Cytochrome P450s (CYPs) are a superfamily of heme monooxygenases generally involved in the clearance of xenobiotics while a subset of isozymes oxidize PUFAs to eicosanoids. Several eicosanoid forming CYPs are overexpressed in tumors, elevating eicosanoid levels and suggesting a key function in tumorigenesis and progression of tumors in the lung, breast, prostate and kidney. This review summarizes the current understanding of CYPs’ involvement in solid tumor etiology and progression providing supporting public data for gene expression from The Cancer Genome Atlas.